Engineering of the microstructures of enzymatic hydrolysis lignin-derived hard carbon anodes for sodium-ion batteries - Shunsheng Yang; Zhihong Zhang; Xueqing Qiu; Lei Zhong; Jiahong Huang; Huiting Zhang; Jianhui Ma; Qingwei Meng; Xihong Zu; Wenli Zhang (Resources Chemicals and Materials, 2023)
Hard carbon is considered as the most commercially applicable anode for sodium-ion batteries. Lignin has the characteristics of sustainable, low cost, high carbon content (>60%) and abundant oxygen functional groups, which is expected to be used as a promising candidate precursor for low-cost hard carbons. The structure and electrochemical performances of hard carbons could be regulated by adjusting carbonization temperature. The microstructure and electrochemical performance of LDHC anode are highly dependent on the carbonization temperature. Increasing carbonization temperature could reduce specific surface area and improve initial coulombic efficiency. The slope and plateau capacity of the LDHC anode could also be adjusted by changing the carbonization temperature. The LDHC prepared at 1200 °C showed the best sodium-ion storage performance, with an initial coulombic efficiency of 78.9% and a reversible sodium-ion storage capacity of 284.7 mAh g−1.